The innovation activity of higher educational institutions of the Republic of Kazakhstan - Sitenko, D.A. (KarSU Publ., 2018)
The monograph examined the content of the concept of innovation activity and its role in the development of the higher education institution. Foreign experience in the development of the innovation activity of universities is systematized. The analysis of the legal framework of the universities’ innovation activity and the evaluation of the scientific and research potential of the Republic of Kazakhstan were provided. A particular attention is paid to assessing the effectiveness of innovation in higher education. The interaction mechanism of the university with the business sector in the process of commercialization of university research at the regional level was presented. The prospects for the establishment of research universities in Kazakhstan are considered. The monograph is intended for researchers, doctoral students, teachers, specialists of government bodies, students of economic faculties.
Keywords: innovation activity; Kazakhstan; higher educational institutions; innovative processes; analysis activity; management; intellectual property